Influence of Secondary Phase Precipitation on Resistance to Intergranular Corrosion of AiSi 316l Austenitic Stainless Steel - Bartova, Katarina; Domankova, Maria; Janovec, Jozef (Communications - Scientific letters of the University of Zilina, 2010)
The AISI 316L steel after cold working of 40% and subsequent annealing at 750°C for 1, 2, 5, 10, 50, or 100 h was investigated. For the microstructure characterization the light microscopy and the transmission electron microscopy were used. To determine the sensitivity to intergranular corrosion the test was performed according to ASTM A 262, practice A. The transition between non-sensitised and sensitised states was found to be between 1 and 2 h of annealing. Sigma, laves and chi phases were identified in all the analyzed conditions. M23C6 was found to start to precipitate between 5 and 10 h of annealing. Sigma, chi, and M23C6 precipitated mainly along the grain boundaries. Laves precipitated mainly inside the grains, and after 50 h of annealing also intergranularly. Time dependent changes in the average metal composition of particular phases were considered as negligible.